2023
DOI: 10.1111/rec.14070
|View full text |Cite
|
Sign up to set email alerts
|

Back from the past? Assessment of nitrogen removal ability of buried historic wetland soils before and after a 1‐year incubation on a restored floodplain

Erin K. Peck,
Shreeram Inamdar,
Jinjun Kan
et al.

Abstract: Stream, floodplain, and wetland restorations enhance water quality and ecological function; however, soil health is prioritized infrequently in restoration planning and monitoring. Buried, historic, hydric soils—common across U.S. mid‐Atlantic valley bottoms beneath legacy sediments—are not included in most floodplain restoration designs, though they may retain favorable biogeochemical characteristics and host legacy microbial communities that could support ecosystem recovery if exhumed and preserved. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…10,39 Both sites were also similar in terms of sediment texture -with both sites having a very high percent (>90%) of silt and clay in the riparian soil profiles. 48 Previous studies have shown that sites that are persistently anoxic and saturated tend to support elevated DNRA rates and provide a favorable habitat for obligate anaerobes and fermentative bacteria that contribute to this process. 19−21 For example, Jantti et al 19 found that soil DNF capacity was almost completely lost, and DNRA dominated in estuarine soils when hypoxia lasted for several months.…”
mentioning
confidence: 99%
“…10,39 Both sites were also similar in terms of sediment texture -with both sites having a very high percent (>90%) of silt and clay in the riparian soil profiles. 48 Previous studies have shown that sites that are persistently anoxic and saturated tend to support elevated DNRA rates and provide a favorable habitat for obligate anaerobes and fermentative bacteria that contribute to this process. 19−21 For example, Jantti et al 19 found that soil DNF capacity was almost completely lost, and DNRA dominated in estuarine soils when hypoxia lasted for several months.…”
mentioning
confidence: 99%